Surface coating affects behavior of metallic nanoparticles in a biological environment - Jurašin, Darija Domazet; Ćurlin, Marija; Capjak, Ivona; Crnković, Tea; Lovrić, Marija; Babič, Michal; Horák, Daniel; Vinković Vrček, Ivana; Gajović, Srećko (Beilstein Journal of Nanotechnology, 2016)
Silver (AgNPs) and maghemite, i.e., superparamagnetic iron oxide nanoparticles (SPIONs) are promising candidates for new medical applications, which implies the need for strict information regarding their physicochemical characteristics and behavior in a biological environment. The currently developed AgNPs and SPIONs encompass a myriad of sizes and surface coatings, which affect NPs properties and may improve their biocompatibility. This study is aimed to evaluate the effects of surface coating on colloidal stability and behavior of AgNPs and SPIONs in modelled biological environments using dynamic and electrophoretic light scattering techniques, as well as transmission electron microscopy to visualize the behavior of the NP. Three dispersion media were investigated: ultrapure water (UW), biological cell culture medium without addition of protein (BM), and BM supplemented with common serum protein (BMP). The obtained results showed that different coating agents on AgNPs and SPIONs produced different stabilities in the same biological media. The combination of negative charge and high adsorption strength of coating agents proved to be important for achieving good stability of metallic NPs in electrolyte-rich fluids. Most importantly, the presence of proteins provided colloidal stabilization to metallic NPs in biological fluids regardless of their chemical composition, surface structure and surface charge. In addition, an assessment of AgNP and SPION behavior in real biological fluids, rat whole blood (WhBl) and blood plasma (BlPl), revealed that the composition of a biological medium is crucial for the colloidal stability and type of metallic NP transformation. Our results highlight the importance of physicochemical characterization and stability evaluation of metallic NPs in a variety of biological systems including as many NP properties as possible.
Keywords: biological fluids; colloidal stability; maghemite; nanoparticles; protein interaction; silver; surface coating

(untitled) - Tai, J.-T.; Lai, C.-S.; Ho, H.-C.; Yeh, Y.-S.; Wang, H.-F.; Ho, R.-M.; Tsai, D.-H. (Langmuir, 2014)

(untitled) - Lohse, S. E.; Murphy, C. J. (J. Am. Chem. Soc., 2012)

(untitled) - Dominguez-Medina, S.; Blankenburg, J.; Olson, J.; Landes, C. F.; Link, S. (ACS Sustainable Chem. Eng., 2013)

(untitled) - Babič, M.; Horák, D.; Trchová, M.; Jendelová, P.; Glogarová, K.; Lesný, P.; Herynek, V.; Hájek, M.; Syková, E. (Bioconjugate Chem., 2008)

(untitled) - Kittler, S.; Greulich, C.; Gebauer, J. S.; Diendorf, J.; Treuel, L.; Ruiz, L.; Gonzalez-Calbet, J. M.; Vallet-Regi, M.; Zellner, R.; Köller, M.; Epple, M. (J. Mater. Chem., 2010)

(untitled) - Yen, H.-J.; Hsu, S.-H.; Tsai, C.-L. (Small, 2009)

(untitled) - Liu, J. Y.; Hurt, R. H. (Environ. Sci. Technol., 2010)

(untitled) - Walters, C.; Pool, E.; Somerset, V. (Toxicol. Environ. Chem., 2013)

(untitled) - Pettibone, J. M.; Gigault, J.; Hackley, V. A. (ACS Nano, 2013)

(untitled) - MacCuspie, R. I.; Allen, A. J.; Hackley, V. A. (Nanotoxicology, 2011)

(untitled) - Loza, K.; Diendorf, J.; Sengstock, C.; Ruiz-Gonzalez, L.; Gonzalez-Calbet, J. M.; Vallet-Regi, M.; Köller, M.; Epple, M. (J. Mater. Chem. B, 2014)

(untitled) - Liu, J. Y.; Sonshine, D. A.; Shervani, S.; Hurt, R. H. (ACS Nano, 2010)

(untitled) - Liu, J. Y.; Wang, Z. Y.; Liu, F. D.; Kane, A. B.; Hurt, R. H. (ACS Nano, 2012)

(untitled) - Stebounova, L. V.; Guio, E.; Grassian, V. H. (J. Nanopart. Res., 2011)

(untitled) - Hotze, E. M.; Labille, J.; Alvarez, P.; Wiesner, M. R. (Environ. Sci. Technol., 2008)

(untitled) - Hussain, S. M.; Braydich-Stolle, L. K.; Schrand, A. M.; Murdock, R. C.; Yu, K. O.; Mattie, D. M.; Schlager, J. J.; Terrones, M. (Adv. Mater., 2009)

(untitled) - Park, E.-J.; Yi, J.; Kim, Y.; Choi, K.; Park, K. (Toxicol. In Vitro, 2010)

(untitled) - Zook, J. M.; MacCuspie, R. I.; Locascio, L. E.; Halter, M. D.; Elliott, J. T. (Nanotoxicology, 2011)

(untitled) - Tejamaya, M.; Römer, I.; Merrifield, R. C.; Lead, J. R. (Environ. Sci. Technol., 2012)

(untitled) - Vidic, J.; Haque, F.; Guigner, J. M.; Vidy, A.; Chevalier, C.; Stankic, S. (Langmuir, 2014)

(untitled) - Marucco, A.; Catalano, F.; Fenoglio, I.; Turci, F.; Martra, G.; Fubini, B. (Chem. Res. Toxicol., 2015)

(untitled) - Leo, B. F.; Chen, S.; Kyo, Y.; Herpoldt, K.-L.; Terrill, N. J.; Dunlop, I. E.; McPhail, D. S.; Shaffer, M. S.; Schwander, S.; Gow, A.; Zhang, J.; Chung, K. F.; et al. (Environ. Sci. Technol., 2013)

(untitled) - Li, X.; Lenhart, J. J.; Walker, H. W. (Langmuir, 2012)

(untitled) - MacCuspie, R. I. (J. Nanopart. Res., 2011)

(untitled) - Sharma, V. K.; Siskova, K. M.; Zboril, R.; Gardea-Torresdey, J. L. (Adv. Colloid Interface Sci., 2014)

(untitled) - Jiang, J.; Oberdörster, G.; Biswas, P. (J. Nanopart. Res., 2009)

(untitled) - Gebauer, J. S.; Treuel, L. (J. Colloid Interface Sci., 2011)

(untitled) - Thanh, N. T. K.; Rosenzweig, Z. (Anal. Chem., 2002)

(untitled) - Schulze, C.; Kroll, A.; Lehr, C.-M.; Schäfer, U. F.; Becker, K.; Schnekenburger, J.; Schulze Isfort, C.; Landsiedel, R.; Wohlleben, W. (Nanotoxicology, 2008)

(untitled) - Gebauer, J. S.; Malissek, M.; Simon, S.; Knauer, S. K.; Maskos, M.; Stauber, R. H.; Peukert, W.; Treuel, L. (Langmuir, 2012)

(untitled) - Segets, D.; Marczak, R.; Schäfer, S.; Paula, C.; Gnichwitz, J.-F.; Hirsch, A.; Peukert, W. (ACS Nano, 2011)

(untitled) - Kohut, A.; Voronov, A.; Peukert, W. (Langmuir, 2007)

(untitled) - Gilbert, B.; Huang, F.; Zhang, H.; Waychunas, G. A.; Banfield, J. F. (Science, 2004)

(untitled) - Min, Y.; Akbulut, M.; Kristiansen, K.; Golan, Y.; Israelachvili, J. (Nat. Mater., 2008)

(untitled) - Zook, J. M.; Halter, M. D.; Cleveland, D.; Long, S. E. (J. Nanopart. Res., 2012)

(untitled) - Treuel, L.; Nienhaus, G. U. (Biophys. Rev., 2012)

(untitled) - Walczyk, D.; Bombelli, F. B.; Monopoli, M. P.; Lynch, I.; Dawson, K. A. (J. Am. Chem. Soc., 2010)

(untitled) - Moerz, S. T.; Huber, P. (Langmuir, 2014)

(untitled) - Monopoli, M. P.; Walczyk, D.; Campbell, A.; Elia, G.; Lynch, I.; Bombelli, F. B.; Dawson, K. A. (J. Am. Chem. Soc., 2011)

(untitled) - Lynch, I.; Salvati, A.; Dawson, K. A. (Nat. Nanotechnol., 2009)

(untitled) - Shannahan, J. H.; Lai, X.; Ke, P. C.; Podila, R.; Brown, J. M.; Witzmann, F. A. (PLoS One, 2013)

(untitled) - Park, M. V. D. Z.; Neigh, A. M.; Vermeulen, J. P.; de la Fonteyne, L. J. J.; Verharen, H. W.; Briedé, J. J.; van Loveren, H.; de Jong, W. H. (Biomaterials, 2011)

(untitled) - El Badawy, A. M.; Silva, R. G.; Morris, B.; Scheckel, K. G.; Suidan, M. T.; Tolaymat, T. M. (Environ. Sci. Technol., 2011)

(untitled) - Martin, M. N.; Allen, A. J.; MacCuspie, R. I.; Hackley, V. A. (Langmuir, 2014)

(untitled) - Horák, D.; Babič, M.; Jendelová, P.; Herynek, V.; Trchová, M.; Pientka, Z.; Pollert, E.; Hájek, M.; Syková, E. (Bioconjugate Chem., 2007)

(untitled) - Horák, D.; Babič, M.; Jendelová, P.; Herynek, V.; Trchová, M.; Likavčanová, K.; Kapcalová, M.; Hájek, M.; Syková, E. (J. Magn. Magn. Mater., 2009)

(untitled) - Vinković Vrček, I.; Žuntar, I.; Petlevski, R.; Pavičić, I.; Dutour Sikirić, M.; Ćurlin, M.; Goessler, W. (Environ. Toxicol., 2014)

(untitled) - Vinković Vrček, I.; Pavičić, I.; Crnković, T.; Jurašin, D.; Babič, M.; Horák, D.; Lovrić, M.; Ferhatović, L.; Ćurlin, M.; Gajović, S. (RSC Adv., 2015)

(untitled) - Milić, M.; Leitinger, G.; Pavičić, I.; Zebić Avdičević, M.; Dobrović, S.; Goessler, W.; Vinković Vrček, I. (J. Appl. Toxicol., 2015)

(untitled) - Kvítek, L.; Panáček, A.; Soukupová, J.; Kolář, M.; Večeřová, R.; Prucek, R.; Holecová, M.; Zbořil, R. (J. Phys. Chem. C, 2008)

(untitled) - Churchman, A. H.; Wallace, R.; Milne, S. J.; Brown, A. P.; Brydson, R.; Beales, P. A. (Chem. Commun., 2013)

(untitled) - Murdock, R. C.; Braydich-Stolle, L.; Schrand, A. M.; Schlager, J. J.; Hussain, S. M. (Toxicol. Sci., 2008)

(untitled) - Cedervall, T.; Lynch, I.; Lindman, S.; Berggård, T.; Thulin, E.; Nilsson, H.; Dawson, K. A.; Linse, S. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - Maiorano, G.; Sabella, S.; Sorce, B.; Brunetti, V.; Malvindi, M. A.; Cingolani, R.; Pompa, P. P. (ACS Nano, 2010)

(untitled) - Simón-Vázquez, R.; Lozano-Fernández, T.; Peleteiro-Olmedo, M.; González-Fernández, Á. (Colloids Surf., B, 2014)

(untitled) - Ravindran, A.; Singh, A.; Raichur, A. M.; Chandrasekaran, N.; Mukherjee, A. (Colloids Surf., B, 2010)

(untitled) - Yang, Q.; Liang, J.; Han, H. (J. Phys. Chem. B, 2009)

(untitled) - Patil, S.; Sandberg, A.; Heckert, E.; Self, W.; Seal, S. (Biomaterials, 2007)

All About Albumin: Biochemistry, Genetics and Medical Applications - Peters, T., Jr (Academic Press, Inc., 1996)

(untitled) - Saptarshi, S. R.; Duschl, A.; Lopata, A. L. (J. Nanobiotechnol., 2013)

(untitled) - Dobrovolskaia, M. A.; Patri, A. K.; Zheng, J.; Clogston, J.; Ayub, D.; Aggarwal, P.; Neun, B. W.; Hall, J. B.; McNeil, S. E. (Nanomedicine, 2009)

(untitled) - Alkilany, A. M.; Nagaria, P. K.; Hexel, C. R.; Shaw, T. J.; Murphy, C. J.; Wyatt, M. D. (Small, 2009)

(untitled) - Khullar, P.; Singh, V.; Mahal, A.; Dave, P. N.; Thakur, S.; Kaur, G.; Singh, J.; Singh Kamboj, S.; Singh Bakshi, M. (J. Phys. Chem. C, 2012)

(untitled) - Casals, E.; Pfaller, T.; Duschl, A.; Oostingh, G. J.; Puntes, V. (ACS Nano, 2010)

(untitled) - Xia, Y.; Xiong, Y.; Lim, B.; Skrabalak, S. E. (Angew. Chem., Int. Ed., 2008)

(untitled) - Goesmann, H.; Feldmann, C. (Angew. Chem., Int. Ed., 2010)

(untitled) - Klaus-Joerger, T.; Joerger, R.; Olsson, E.; Granqvist, C.-G. (Trends Biotechnol., 2001)

(untitled) - Lowenstam, H. A. (Science, 1981)

(untitled) - Spring, S.; Schleifer, K.-H. (Syst. Appl. Microbiol., 1995)

(untitled) - Schüler, D.; Frankel, R. B. (Appl. Microbiol. Biotechnol., 1999)

(untitled) - Kajander, E. O.; Çiftçioglu, N. (Proc. Natl. Acad. Sci. U. S. A., 1998)

(untitled) - Rivadeneyra, M.-A.; Delgado, G.; Soriano, M.; Ramos-Cormenzana, A.; Delgado, R. (Curr. Microbiol., 1999)

(untitled) - Keefe, W. E. (Infect. Immun., 1976)

(untitled) - Klaus, T.; Joerger, R.; Olsson, E.; Granqvist, C.-G. (Proc. Natl. Acad. Sci. U. S. A., 1999)